PENGARUH MOTIVASI DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN KENDARAAN RODA DUA HONDA - RAHMAN, NURUL HIDAYAH A; SUMAMPOUW, HARRY J.; SAMBUL, SOFIA A.P (JURNAL ADMINISTRASI BISNIS, 2016)
Abstract This research was based a decrease in sales of Honda motorcycles in the period 2011-2014.This sales decline shows a decrease in consumer buying decisions on Honda motorcycle productsthat can be formulated in this research that how consumers buying decision in the midst ofmotorcycle competition phenomenon becoming more strictly based on the consumer motivation, andconsumer attitudes. The aim of the research is to influence of motivation and consumer attitudestoward buying decision of the Honda motorcycles.This research uses quantitative and qualitative methods. Data collected by questionnaireand interview techniques. The respondents in this research are 100 people who fulfill in one of fivecriteria; initiating, influencing, decision making, buying, and using Honda motorcycles in thedistrict of mapanget. Two hypotheses are formulated and tested using Regression Analysis. Theresult shows that consumers motivation, and consumer attitudes have significant relationship withbuying decision. Consumer motivation has higher influences for buying decisions than consumerattitudes.Keywords: Buying Decision, Consumer Motivation, Consumer Attitudes.